Mixed emotional experience in urban public spaces: the role of CCTV surveillance - Doorn, Janne van (Criminological encounters, 2023)
From previous research it seems that the (emotional) experience of CCTV surveillance in urban public spaces is mixed, and depends on the specific urban context. This ambivalence underscores the importance of taking a broader perspective on the measurement and effects of CCTV experience than has previously been done. The current study therefore reports on the effects of the presence or absence of CCTV surveillance on the emotions people experience in urban public spaces. In doing so, we have used two typical urban spaces that more generally are expected to differ in the emotional experience: an alley with graffiti at dusk versus a green park at daytime. Where previous studies have mainly focused on the emotions fear and worry in relation to the presence of CCTV surveillance in urban public spaces, the current study aims to explore a broader emotional palette. More specifically, we have looked at the negative emotions fear, worry, anger, disgust, shame, guilt, and sadness, and the positive emotions trust, awe, and happiness. Results among 1003 members of the general public show that the emotional experience of (both) these urban environments is very diverse, and not limited to the presence or absence of fear and worry. Furthermore, adding CCTV as an intervention can be helpful in reducing worry in an alley, but is shown to be counterproductive (lower happiness and higher worry) in more neutral surroundings such as a park.